Study On Romania's Potential in Achieving Agricultural Mountain Products - Andreea D. GIUCA; Veronica BACIU (Communications of International Proceedings, 2022)
The main objective of this paper is to promote the concept of "mountain product", analyzing the structure of agri-food products from mountain areas and its characteristics, taking into account the fact that mountain products have superior qualities determined by the specifics of the geographical area. Mountain products also play a key role in building the identity of communities in these areas, with identity being the hallmark of added value to agri-food products. The mountain product has become a recognized brand as a geographical indication, taking into account the complementary elements of quality, ecological origin and authenticity. The valorisation of the products within the mountain farms will produce beneficial effects both for the farmers, by obtaining complementary incomes, and for the consumers who are beneficiaries of some healthy agri-food products. Romania registered in 2021, a number of 3,147 mountain products and 1,164 producers of mountain products, the trend being an increasing one, considering the fact that in the first month of 2022, 40 mountain products were registered.
Keywords: mountain area; mountain product; manufacturers